Commercialization of research results from universities to businesses in Vietnam: Current situation and solution - Luat, Ho Ngoc; Kha, Nguyen Thi (Journal SCIENCE AND TECHNOLOGY POLICIES AND MANAGEMENT, 2017)
Technology transfer and commercialization of research results are the actual issues which interest a lot of domestic and international researchers and management agencies. Today, science and technology (S&T) becomes a decisive factor in socio-economic growth and development. Commercialization of research results actively contributes to fostering the development of S&T market and accelerate the introduction of research results into practical life. This article will discuss the concept of "commercialization of research results" and its implications; identify the status of commercialization of research results from universities to businesses in Vietnam in recent years; analyze difficulties and propose policies to promote the commercialization of research results from universities to businesses. Code: 14121301